(untitled) (Research, Society and Development, 2020)
Objective: To analyze the presence of psychological distress in homeless women. Method: Descriptive, exploratory study with a qualitative approach, using the theoretical framework of thematic content analysis. Held in a type II reception center in São Paulo. Interview with instrument on sociodemographic profile and morbidity and guiding questions. Interviews were audio recorded, transcribed in full and interpreted according to content analysis. Results: Sixteen homeless women participated in the study, all of them experienced psychological suffering before the homelessness and once in it, he was aggravated by the adversities in the attempt to survive, in the midst of daily life permeated by subhuman conditions, prejudices, idleness, invisibility social, impediments to reintegration into the labor market, serious violations of human rights and the violence suffered, including that of the State. Main manifestations identified were changes in mood, sleep and appetite, emotional stress, suicide attempts, constant crying, anxiety, nervousness and psychosomatic symptoms. Conclusion: the presence of psychological suffering, was due to a capitalist, sexist and patriarchal system that corroborates social vulnerability through social inequality and exclusion.